The associations between dietary flavonoid intake and hyperlipidemia: data from the national health and nutrition examination survey 2007–2010 and 2017–2018 - Wan, Yingying; Ma, Dan; Yu, Linghua; Tian, Wende; Wang, Tongxin; Chen, Xuanye; Shang, Qinghua; Xu, Hao (Frontiers in Nutrition, 2024)
Abstract Background Hyperlipidemia is a worldwide health problem and a significant risk factor for cardiovascular diseases; therefore, it imposes a heavy burden on society and healthcare. It has been reported that flavonoids can increase energy expenditure and fat oxidation, be anti-inflammatory, and reduce lipid factor levels, which may reduce the risk of hyperlipidemia. However, the relationship between the prevalence of hyperlipidemia and dietary flavonoid intake in the population remains unclear. Methods This study included 8940 adults from the 2007–2010 and 2017–2018 National Health and Nutrition Examination Surveys (NHANES). The relationship between dietary flavonoid intake and the prevalence of hyperlipidemia was analyzed using weighted logistic regression and weighted restricted cubic spline. Results We found an inverse relationship between subtotal catechins intake and hyperlipidemia prevalence in the third quartile [0.74 (0.56, 0.98), p = 0.04] compared with the first quartile. The prevalence of hyperlipidemia and total flavan-3-ol intake in the third quartile were inversely correlated [0.76 (0.59, 0.98), p = 0.02]. Total anthocyanin intake was inversely related to the prevalence of hyperlipidemia in the third quartile [0.77 (0.62, 0.95), p = 0.02] and the fourth quartile [0.77 (0.60, 0.98), p = 0.04]. The prevalence of hyperlipidemia was negatively correlated with total flavonols intake in the fourth quartile [0.75 (0.60, 0.94), p = 0.02]. Using restricted cubic splines analysis, we found that subtotal catechins intake and total flavan-3-ol intake had a nonlinear relationship with the prevalence of hyperlipidemia. Conclusions Our study may provide preliminary research evidence for personalizing improved dietary habits to reduce the prevalence of hyperlipidemia.